2020
DOI: 10.1177/1833358320929776
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation into clinical documentation: why do clinicians document the way they do?

Abstract: Background: Clinical documentation is a fundamental component of patient care. The transition from paper based to electronic medical records/electronic health records has highlighted a number of issues associated with documentation practices including duplication. Developing new ways to document the care provided to patients and in turn, persuading clinicians to accept a change, must be supported by evidence that a change is required. In Australia, there has been a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Findings might, therefore, reflect overreporting. Other factors, such as time, technical issues, knowledge, and motivation, have been associated with documentation practice but these have not been addressed in this study [1, 20, 27]. Further research is needed to explore whether these factors are associated with the documentation of goals and outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Findings might, therefore, reflect overreporting. Other factors, such as time, technical issues, knowledge, and motivation, have been associated with documentation practice but these have not been addressed in this study [1, 20, 27]. Further research is needed to explore whether these factors are associated with the documentation of goals and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the widespread use of electronic health record (EHR) systems in Scandinavia may facilitate this process [22–24], a number of studies have revealed inadequate documentation of patients' goals and outcomes [2–4, 13, 25, 26], not least in nutrition care [14, 15]. Factors such as work experience and clinical judgement may influence documentation practices [1, 20, 27]. For example, higher education among nurses is associated with greater expertise and improved quality of care [28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding indicates that the intersection of several allied health disciplines in providing care to patients with multiple conditions (e.g., increased social, dietary, physical, and communication support needs) is potentially splintering the health information. The complexity of clinicians' documentation practices is influenced by environmental, systemic, and personal factors (Rowlands et al, 2020). This suggests that health systems and documentation management should recognise, value, and promote complexity in the patient and in the clinician.…”
Section: Recognising Complexity In Documentation and Clinical Coding ...mentioning
confidence: 99%